PEMANFAATAN MEDIA PEMBELAJARAN KANTONG KIPAS PINTAR (KKP) DALAM KETERAMPILAN MENULIS PUISI - Robertus Adi Sarjono Owon; Muhammad Lautama; Waharini Waharini (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
The problem in this research raises the issue of increasing poetry writing skills through the smart fan pocket (SFP) media. The purpose of the study was to improve the poetry writing skills of eighth grade students in Indonesia subjects. the type of this research is CAR namely classroom action research and this is a qualitative descriptive reseach, this research was carried out with subjects consisting of 30 students, conducted into two cycles namely cycle I an cycle II, data collection in the research namely observation instruments an learning outcomes test, activities observation to observe students and educators. Learning outcomes instruments are carried out to determine the absorption and percentage of student learning outcomes. Complete learning set by the school for Indonesian language subjects for VIII grade students is KKM 70. From the results of the study it can be concluded in circle I shows an increase in poetry writing skills where there is no completeness with a value of 40% and an average of 63. Cycle II shows an increase in poetry writing skills with a completeness value of 90% and an average of 82 and the percentage of students reaches more.